Kekhasan Pengajaran Bahasa Mandarin di Indonesia - Sutami, Hermina (UI Scholars Hub, 2007)
1998 was the year of Mandarin teaching resurrection in Indonesia after 30 years prohibited. Since then, many schools begin to teach Mandarin as an extracurricular subject. In the last two years it becomes an intracurricular subject. Since there was no Chinese school for almost 30 years, consequently there was no publication on Mandarin student's book, no Mandarin teachers. Nowadays, suddenly Mandarin teachers, student's book was highly needed. Many schools use Singapore/Taiwan's book. This rises problems, because Singapore/Taiwan's students language circumstance is different from Indonesian students. The result is far from what we expected. This article proposed some aids based on the need of Indonesian's student. Department of Education should set up a team consisting of Indonesian experts in Mandarin language teaching and Chinese linguistic to compile syllabus, student's book. It should base on Indonesian Language Politics and the need of Indonesian's student which differ from Chinese schools 30 years ago.